ENGLISH DIPHTHONGS & STUDENTS’ PERCEPTION: AN ANALYSIS FROM PHONOLOGICAL POINT OF VIEW - Firghy, Siti Aisyah Mutiara; Bochari, Siska; Hastini, Hastini; Mukrim, Mukrim (Universitas Muhammadiyah Metro, 2024)
Certain English sounds are absent from Indonesian, making pronating English diphthongs challenging for certain students. It is challenging for students to pronounce English diphthongs correctly due to various internal and external factors, including their ignorance of when to pronounce them based on their type and position. The researchers attempt to examine how difficult it is for the students and how they perceive English diphthongs based on the issue they are facing. This study's objectives are the most challenging diphthongs pronounced by students, the most difficult diphthong position, and the degree to which students struggle with pronouncing English diphthong sounds. The design of this study is quantitative and descriptive. Forty-two students comprise the study's sample, and their answers to an oral exam and questionnaire are used to gather data. The researchers found 97 errors in the closing type and 191 in the centring type of diphthongs uttered by the students. The most challenging position of diphthongs in their pronunciation is the centering position (eə, ɪə, ʊə). In addition, five factors are becoming the reason for students' difficulty in pronouncing English diphthong sounds. They are (1) the students have less confidence while pronouncing words, (2) each student has different and limited skills, (3) the lack of motivation from the students causes difficulties in the teaching and learning process, (4) the family environment is very influential in the language development of the students, and (5) the social environment is also one of the influences in the language development of the students. The implication of this study can be in the field of linguistics and education, for example, phonological theories and pedagogical strategies.